PMTCT, HAART, and Childbearing in Mozambique: An Institutional Perspective (2009)
Maternal and Child Health (MCH) units, where VCT/PMTCT/HAART have been integrated with traditional services, play a critical role in the connection between the massive HAART rollout and reproductive behavior. In this article, we use data from semi-structured interviews with MCH workers and ethnographic observations carried out in southern Mozambique to explore this role from the institutional perspective. We find that, along with logistical and workload problems, the de facto segregation of PMTCT/HAART clients within the “integrated” MCH system and the simplistic and uncompromising message discouraging further fertility and stressing condom-based contraception, may pose serious challenges to a successful formulation and implementation of reproductive goals among seropositive clients. Although the recency of PMTCT/HAART services may partly explain these challenges, we argue that they are due largely to cultural miscommunication between providers and clients. We show how the cultural gap between the two is bridged by community activists and peer interactions among clients.